Management and Marketing Assistance Program at CV Sweetroom - Andita, Cindy; Audita Nuvriasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
A management system is a collection or combination of processes that start from planning, organizing, implementing, monitoring and evaluating, and work together to achieve certain goals in an efficient and effective way. Sweetroom does not yet have a management system, so it becomes an obstacle in implementing work coordination and organizational communication. The goal of a management system is to obtain something of better value by exerting effort. At Sweetroom the Standard Operating Procedure (SOP) for each work unit is not yet available, so it is necessary to prepare SOPs for work activities in each work unit. The results obtained from preparing the SOP are increased employee discipline and increased sales in Sweetroom.